Reducing antigenicity of β-lactoglobulin, probiotic properties and safety evaluation of Lactobacillus plantarum AHQ-14 and Lactobacillus bulgaricus BD0390. (August 2021) - Meng, Lingying; Zhu, Xuemei; Tuo, Yanfeng; Zhang, Heping; Li, Yue; Xu, Chao; Mu, Guangqing; Jiang, Shujuan
Abstract: Probiotics are important bacteria because they are beneficial to human health. Two lactic acid bacteria (LAB) strains capable to hydrolyze immuno-reactive β-lactoglobulin (β-Lg) proteins in milk, including AHQ-14 isolated from Chinese Xinjiang district traditional dairy products and identified as Lactobacillus plantarum by 16S rRNA gene sequences analysis, and Lactobacillus bulgaricus BD0390 kindly donated by Bright Dairy Company (Shanghai, China), were investigated for their probiotic traits and safety. Lactobacillus plantarum AHQ-14 and Lactobacillus bulgaricus BD0390 were tested their ability to lower β-Lg antigenicity, bile salt hydrolase (BSH) activity, survival rate in gastrointestinal and adhesion capacity to HT-29 cells. For preliminary safety assessment, L.plantarum AHQ-14 and L.bulgaricus BD0390 were tested for hemolytic activity, biogenic amines (BAs) production and for their antibiotic resistance. Results showed that L.plantarum AHQ-14 and L.bulgaricus BD0390 were γ-hemolytic and showed high abilities to adhere to HT-29 cells. They exhibited higher survival rates than the control ( Lactobacillus rhamnosus GG) under simulated gastric conditions. Both strains produced a small amount of BAs, similar to or even lower than the BAs content in the regularly consumed foods. Furthermore, they showed sensitivity towards conventionally used antibiotics. In conclusion, L.plantarum AHQ-14 and L.bulgaricus BD0390 possessed good characteristics as potential probiotic for functional fermented food in the future.